Календарное время северных самодийцев - Leisiö, Larisa; Lublinskaya, Marina (Helsingin yliopiston kirjasto, 2022)
In this paper we discuss the names of the periods of the annual cycle of the Northern Samoyeds, the words for year, the seasons and the months. We show that these names are nature-centered and that the symbiosis with nature was the basis of life and livelihood of the Northern Samoyeds.